The influence of Louvain teaching on Jan Baptist van Helmont’s adoption of Paracelsianism and alchemy - Hedesan, DG (Taylor and Francis, 2021)
This article investigates the extent to which Louvain (Leuven) teaching could provide the foundations of a new learning and philosophy that included Paracelsianism and alchemy. The particular lens is through Van Helmont’s studies in Louvain, taking place in the 1590s. It shows that teaching at Louvain had a profound impact on Van Helmont’s thought. The paper further points out that Van Helmont's learning process did not include only traditional university courses, but also classes at the Jesuit college, and practical learning through Jesuits and artisans.